Estimating COVID Risk During a Period of Pandemic Decline - Inglis, Timothy J. J.; McFadden, Benjamin; Macali, Anthony (Frontiers in Public Health, 2021)
Background. Many parts of the world that succeeded in suppressing epidemic coronavirus spread in 2020 have been caught out by recent changes in the transmission dynamics of SARS-CoV-2. Australia’s early success in suppressing COVID-19 resulted in lengthy periods without community transmission. However, a slow vaccine rollout left this geographically isolated population vulnerable to leakage of new variants from quarantine, requiring internal travel restrictions, disruptive lockdowns, contact tracing and testing surges. Methods. To assist long term sustainment of limited public health resources, we sought a method of continuous, real-time COVID-19 risk monitoring that could be used to alert non-specialists to the level of epidemic risk on a sub-national scale. After an exploratory data assessment, we selected four COVID-19 metrics used by public health in their periodic threat assessments, applied a business continuity matrix and derived a numeric indicator; the COVID-19 Risk Estimate (CRE), to generate a daily spot CRE, a three day net rise and a seven day rolling average. We used open source data updated daily from all Australian states and territories to monitor the CRE for over a year. Results. Upper and lower CRE thresholds were established for the CRE seven day rolling average, corresponding to risk of sustained and potential outbreak propagation, respectively. These CRE thresholds were used in a real-time map of Australian COVID-19 risk estimate distribution by state and territory. Conclusions. The CRE toolkit we developed complements other COVID-19 risk management techniques and provides an early indication of emerging threats to business continuity. Contemporaneous CRE data presented in a simplified geographic interface will assist non-experts to understand fluctuations in COVID-19 risk that are not apparent from case numbers alone, and present an opportunity for earlier introduction of control measures.